Maternal diet in pregnancy and offspring height, sitting height, and leg length. Issue 6 (23rd May 2005) - Leary, Sam; Ness, Andy; Emmett, Pauline; Davey Smith, George; ,
Abstract : Study objective: To examine the association between maternal diet in pregnancy and offspring height, sitting height, and leg length. Design: Cohort study. Setting: South west England. Participants: 6663 singletons (51% male) enrolled in the Avon longitudinal study of parents and children, with information on their mother's diet in late pregnancy (obtained by food frequency questionnaire) and their own height recorded at age 7.5 years. Main results: Before adjustment, maternal magnesium, iron, and vitamin C were the nutrients most consistently associated with offspring height and its components. However, adjusting for potential confounders weakened all relations considerably. For example, a standard deviation (SD) increase in magnesium intake was associated with a 0.10 (−0.07, 0.14) SD unit increase in height before adjustment, which was reduced to 0.05 (0.01, 0.08) SD units after adjustment, and a SD unit increase in iron intake was associated with 0.08 (0.05, 0.12) and 0.04 (0.01, 0.08) SD unit increases in height before and after adjustment respectively. No other dietary variables were associated with height or its components after adjustment. Conclusions: These findings do not provide evidence that maternal diet in pregnancy has an important influence on offspring height, sitting height, or leg length in well nourished populations, although effects may emerge as offspring become older.